Is perception reality? Associations among "light" cigarettes and number of cigarettes smoked per day. (1st March 2023) - Freitas-Lemos, Roberta; Tegge, Allison N.; Athamneh, Liqa N.; Yeh, Yu-Hua; Craft, William H.; Stein, Jeffrey S.; Smith, Tracy T.; Stepanov, Irina; Rees, Vaughan W.; Cummings, K. Michael; O'Connor, Richard J.; Shields, Peter G.; et al.
Abstract: Introduction: Cigarette filter ventilation and light descriptors are associated with lowered perceptions of risk and smoking more cigarettes per day (CPD). This study examined the relationship between usual cigarette ventilation, perception, and CPD. Methods: A crowdsourced sample (N = 995) of individuals who smoke higher-ventilated (=>20% ventilation) or lower-ventilated (=<10% ventilation) cigarettes identified their usual cigarette as "light" or "full flavor", and reported their average CPD. Results: We found: 1) no association between ventilation status and perception of light versus full flavor (AUC=0.58), with the inaccurate perception being more prevalent in younger individuals (p = 0.041) and those who smoke L&M (73%, p < 0.001) and Camel (61%, p = 0.006) brands; and 2) perception, but not ventilation of usual cigarette, was significantly associated with CPD (p = 0.006), with individuals who perceived their cigarettes as light reporting an average of 13% more cigarettes per day (2.6 CPD), compared to those who perceived their cigarette as full flavor. Conclusions: Perceptions of light versus full-flavor, but not ventilation status, predicted CPD. These findings may inform anti-smoking health communication strategies and smoking cessation interventions. Implications : Tobacco control policies should eradicate the perception of cigarettes as light or full-flavored. Future research investigating the associations between cigarette filter ventilation and smoking behavior should consider the confounding effects that may lie in an individual's perceptions of their cigarettes. Highlights: No significant association between ventilation and perception of light or full flavor. Perception of light versus full flavor associated with increased smoking. Higher levels of cigarette filter ventilation not associated with increased smoking.